Os desafios da política de integração regional e a governação multinível na Comunidade Econômica dos Estados da África Ocidental - Coutinho, Kathleen Rocheteau Gomes; Canto, Paulino Oliveira do (Monções: Revista de Relações Internacionais da UFGD, 2018)
Regional integration is a complex process of supranational relations in order to respond to the challenges of the national, regional and international conjuncture. It is understood that in order to respond to the challenges of regionalization in this case, the Economic Community of West African States (ECOWAS) must gradually move to multilevel governance, which therefore plays a crucial role in the development of regional integration policies. Based on the neofunctionalist theory, this paper has as main objective to understand the influence of multilevel governance in the development of regional integration policy in ECOWAS. This article is based on a qualitative analysis, using data collected through documents from secondary sources. This is a comprehensive analysis of multilevel governance and the challenges of regional integration policy in ECOWAS. The results, after a systematic analysis of the available data, show that multilevel governance in ECOWAS began with the structural and regulatory reforms of the Revised Treaty of 1993 and a number of other mechanisms which allowed the sharing of the objectives of the Community with the other institutions, in addition to the Conference of Heads of State and Government and non-state actors.
Keywords: CEDEAO; Comunidade Económica dos Estados da África Ocidental; ECOWAS; Governação Multinível; Multilevel Governance; Neofuncionalismo; Regional Integration Policy

O papel da integração regional como mecanismo de inserção internacional e de promoção de desenvolvimento: um estudo de caso sobre a SADC - Calich, Ana Paula de Mattos (Universidade Federal do Rio de Janeiro, 2018)
A intensificação dos processos de integração regional no pós-Guerra Fria e a ascensão de alguns países do Sul global trouxeram para o campo das Relações Internacionais o desafio da atualização do estudo acerca do tema. Partindo do entendimento que estas regiões periféricas possuem uma lógica singular, o presente trabalho busca ver os blocos de integração estabelecidos neste contexto como uma forma de modificar a inserção internacional desfavorável e promover desenvolvimento nos países-membros. Para validar tal análise, a Comunidade para o Desenvolvimento da África Austral (SADC) foi selecionada como estudo de caso, fazendo-se o esforço de correlacionar as políticas do bloco com as transformações econômicas, políticas e sociais que ocorreram nos anos de vigência da integração.
Keywords: Desenvolvimento; Inserção Internacional; Integração Regional; SADC; África Austral